2006
DOI: 10.1002/jbt.20114
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of p‐coumaric acid in the perfused rat liver

Abstract: The p-coumaric acid, a phenolic acid, occurs in several plant species and, consequently, in many foods and beverages of vegetable origin. Its antioxidant activity is well documented, but there is also a single report about an inhibitory action on the monocarboxylate carrier, which operates in the plasma and mitochondrial membranes. The latter observation suggests that p-coumaric acid could be able to inhibit gluconeogenesis and related parameters. The present investigation was planned to test this hypothesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
(36 reference statements)
0
15
0
1
Order By: Relevance
“…The antioxidant activity reported for p-coumaric acid could help reduce oxidative stress and, consequently, the liver cellular damage (Pereira et al, 2009). In addition, it is likely that p-coumaric acid in the extract inhibits gluconeogenesis in the liver by inhibiting pyruvate transport into the mitochondria, as reported Lima et al (2006). Other of the major compounds of C. ficifolia extract, salicin, also could contribute to the liver-protective effect due its reported neuroprotective and anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 80%
“…The antioxidant activity reported for p-coumaric acid could help reduce oxidative stress and, consequently, the liver cellular damage (Pereira et al, 2009). In addition, it is likely that p-coumaric acid in the extract inhibits gluconeogenesis in the liver by inhibiting pyruvate transport into the mitochondria, as reported Lima et al (2006). Other of the major compounds of C. ficifolia extract, salicin, also could contribute to the liver-protective effect due its reported neuroprotective and anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 80%
“…While several studies have shown that chemical inhibition of MPC activity decreases liver glucose production (Lima et al, 2006; Martin-Requero et al, 1986; Rognstad, 1983; Thomas and Halestrap, 1981) other studies using small molecule inhibitors of the MPC (Rognstad, 1983) or hepatocytes expressing a hypomorphic MPC2 allele (Vigueira et al, 2014), failed to demonstrate a strong effect of MPC impairment on gluconeogenesis. Our studies may explain a lack of effect of MPC inhibition on gluconeogenesis by elucidating a compensatory pathway that is operant when mitochondrial pyruvate flux is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of pyruvate transport into the mitochondria diminishes glucose synthesis from substrates such as lactate and alanine as amply demonstrated in experiments with the classical inhibitor of pyruvate transport cyano-4-hydroxycinnamic acid 33 and also in experiments with p-coumaric acid. 34 Lactate must be first transformed into pyruvate before entering the gluconeogenic pathway. Inhibition of pyruvate transport limits the availability of this compound to the intramitochondrial pyruvate carboxylase which is by far the most important regulatory enzyme, as can be deduced from its flux control coefficient (between 56 and 75%) that greatly surpasses those ones of the other enzymes including phosphoenolpyruvate carboxykinase (between 0.2 and 5%).…”
Section: Discussionmentioning
confidence: 99%